The Practice of Khuruj Fisabilillah in Shaping the Religious Character of Youth in Jama’ah Tabligh: A Living Quran Study - M. Ihsan; Hery Sahputra (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study addresses the limited scope of Living Quran research that explores khuruj fi sabilillah as a medium for the internalization of Quranic values in shaping the religious character of youth. The research aims to examine the understanding of Jama’ah Tabligh youth in an Indonesian community regarding the practice of khuruj fi sabilillah, to identify the Quranic values received and internalized through this practice, and to explain the supporting and constraining factors in the formation of religious character. Employing a qualitative method with a descriptive-interpretative approach within the Living Quran framework, data were collected through in-depth interviews, non-participant observation, and documentation involving Jama’ah Tabligh youth and amir actively engaged in khuruj activities. Data analysis was conducted through reduction, presentation, verification, and thematic interpretation. The findings demonstrate that khuruj fi sabilillah functions not only as a missionary activity but also as a process of experiencing, receiving, and actualizing Quranic teachings in socio-religious life. This practice contributes to strengthening worship discipline, responsibility, Islamic brotherhood (ukhuwah Islamiyah), sacrifice, and self-control among youth. The study enriches Living Quran scholarship, particularly in relation to contemporary da’wah movements and the development of religious character among Muslim youth.